Transaksi Jual Beli Foreign Exchange Secara Online Perspektif Hukum Islam - M. Azmi (TERAJU: Jurnal Syariah dan Hukum, 2020)
This article The development of the latest technology cannot be separated from its influence on the lifestyle trends and human economic behavior, as well as investment behavior. Forex online trading includes financial investments, especially in investments in the field of money markets and commodity futures exchanges. The author is of the view that the online forex trading transaction law is haram because it does not fulfill the pillars and conditions of sale and purchase and contains elements of gharar, maisir (gambling), usury and violates the provisions of al-sharf that is the element of speculation / chance, and this investment is classified in trading futures (future market) means the place / facility of buying and selling contracts for a number of commodities or financial instruments at a certain price whose agreed delivery of goods will be carried out in the future.